The Long-Run Impacts of Adult Deaths on Older Household Members in Tanzania - Adhvaryu, Achyuta R.; Beegle, Kathleen (2012)
HIV/AIDS is drastically changing the demographic landscape in high-prevalence countries in Africa. The prime-age adult population bears the majority of the mortality burden. These missing prime-age adults have implications for the socioeconomic well-being of surviving family members. This study uses a 13-year panel from Tanzania to examine the impacts of prime-age mortality on the time use and health outcomes of older adults, with a focus on long-run impacts and gender dimensions. Prime-age deaths are weakly associated with increases in working hours of older women when the deceased adult was co-resident in the household. The association is strongest when the deceased adult was living with the elderly individual at the time of death and for deaths in the distant past, suggesting that shorter-run studies may not capture the full extent of the consequences of adult mortality for survivors. Holding more assets seems to buffer older adults from having to work more after these shocks. Most health indicators are not worse for older adults when a prime-age household member died, although more distant adult deaths are associated with an increased probability of acute illness for the surviving elderly. For deaths of children who were not residing with their parents at baseline, the findings show no impact on hours worked or health outcomes.